A Novel Modified Bat Algorithm to Solve the Practical Economic Dispatch - SEDAGHATI Reza (Journal of Electrical and Electronics Engineering, 2022)
Economic load dispatch is one of the significant problems in production planning procedures necessary for power generation systems, as its goal is to determine the level of output that will lead to minimization of operating cost. This study presents a new method for solving the non-convex economic dispatch problem with a set of practical constraints including ramp rate limits, valve point effects, prohibited operating zones(POZ), spinning reserve, and multi-fuel power generation. Considering the inability of classical methods to model these practical constraints, a new bat optimization algorithm was used to minimize the fuel cost objective function. To overcome the high complexity associated with the optimization of large economic dispatch problems, anew modification method was applied to basic bat algorithm to improve its population diversity, its ability to avoid local minima, and its convergence rate. The proposed method was tested on models of 40 bus IEEE-standard systems, and satisfactory results were obtained.